Power flow optimization for grid connected inverter using evolutionary algorithm and additional control loop - Carniato, L. A.; Godoy, R. B.; Pinto, J. O P; Canesin, C. A. [UNESP]; Garcia, R. C. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
In this work it is proposed to validate an evolutionary tuning algorithm in plants composed by a grid connected inverter. The optimization aims the tuning of the slopes of P-Ω and Q-V curves so that the system is stable, damped and minimum settling time. Simulation and experimental results are presented to prove the feasibility of the proposed approach. However, experimental results demonstrate a compromising effect of grid frequency oscillations in the active power transferring. In addition, it was proposed an additional loop to compensate this effect ensuring a constant active power flow. © 2011 IEEE.
Keywords: grid-connected operation; Inverters; modeling; optimization; power oscillations minimization; Active power; Active power flow; Additional control; Evolutionary tuning; Grid connected inverters; Grid frequency oscillations; Grid-connected operation; Power flows; Power oscillations; Settling time; Electric inverters; Models; Optimization; Power electronics; Tuning; Evolutionary algorithms